2005
DOI: 10.1007/s11167-005-0435-4
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Thermal Degradation of Copolymers of Acrylamide with Sodium Acrylate in Aqueous Solutions

Abstract: The kinetics of thermal degradation of commercial samples of copolymers of acrylamide with sodium acrylate of various molecular characteristics in water and 1.5% NaCl aqueous solutions at 40 380oC was studied viscometrically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Normally, gel permeation chromatography (GPC) is a reliable method for measuring polymer molecular weights. However, in the literature molecular weights of AAm/AAc copolymer have mainly been determined by intrinsic viscometry or light scattering . This is because accurately measuring the molecular weight of high molecular weight polyelectrolytes with GPC is especially complicated, due to the polyelectrolyte nature of the copolymer that affects the mechanism of separation in the GPC columns.…”
Section: Introductionmentioning
confidence: 99%
“…Normally, gel permeation chromatography (GPC) is a reliable method for measuring polymer molecular weights. However, in the literature molecular weights of AAm/AAc copolymer have mainly been determined by intrinsic viscometry or light scattering . This is because accurately measuring the molecular weight of high molecular weight polyelectrolytes with GPC is especially complicated, due to the polyelectrolyte nature of the copolymer that affects the mechanism of separation in the GPC columns.…”
Section: Introductionmentioning
confidence: 99%
“…26 However, in another study using the Mark-Houwink equation method, it was found that the M w of HPAM (hydrolysis degree: 28%) decreased from 1.6 Â 10 6 to 1.35 Â 10 6 , 0.48 Â 10 6 , 0.87 Â 10 6 , 1.14 Â 10 6 and 1.26 Â 10 6 g mol À1 even aer being treated at 26, 40, 60, 70 and 80 C for 4 hours. 27 It seemed that the SLS and GPC methods exhibited similar results, but the Mark-Houwink equation method gave some different results. The latter one gives the measurement results based on the intrinsic viscosity of polymer solutions, which might be affected by the change of the hydrolysis degree.…”
Section: The Molecular Weight (M W ) Changes Of Hpammentioning
confidence: 99%
“…Polyacrylamide-based (PAM-based) polymers are known to be sensitive and susceptible to degradation during various applications [41][42][43][44][45]. For example, PAM-based polymers are prone to mechanical degradation when exposed to turbulent flow in channels, leading to chain scission [46][47][48][49].…”
mentioning
confidence: 99%